2020
DOI: 10.4236/jss.2020.89004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Tertiary Education in Bangladesh: Students’ Perspectives

Abstract: The present study sought to explore the impact of COVID-19 pandemic on tertiary education in Bangladesh through the students' perspectives by using a qualitative research design. The participants were fifty university students who took part in semi-structured interviews. The thematic analysis method was used for data analysis. Numerous unprecedented disruptions in students' learning, decrease in motivation and study hours, and various physical, mental, and economic problems regarding academic studies were prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
139
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 26 publications
14
139
1
5
Order By: Relevance
“…It is interesting to note that students didn"t seem to enjoy this temporary break from academic life, on the contrary, they rather preferred to go on as usual with their studies. These findings are in accordance with studies in other countries (Dutta and Smita, 2020), that came to the same results, despite cultural differences that could be mentioned among students from different countries and civilizations.…”
Section: Discussionsupporting
confidence: 93%
“…It is interesting to note that students didn"t seem to enjoy this temporary break from academic life, on the contrary, they rather preferred to go on as usual with their studies. These findings are in accordance with studies in other countries (Dutta and Smita, 2020), that came to the same results, despite cultural differences that could be mentioned among students from different countries and civilizations.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike Zia's (2020) quantitative study that discovered students had trouble in technology adaptability with the new teaching model. Nevertheless, students did raise the concern on poor internet connections would interfere with the online learning experience which comprehends with Dushkevych et al's (2020), Zhang et al's (2020), Mohmmed et al's (2020), Blizak et al's (2020) and Dutta & Smita's (2020) research studies. This issue has been the main concern for many as every possible way of online course delivery relies on internet services.…”
Section: Technological Tools and Technical Supportmentioning
confidence: 80%
“…In the relation to this study, Zhong (2020) and Crawford et al (2020) claimed that minimal resourced institutions and limited access to technology or the internet impacted students' ability to engage and participate in the online environment. Similarly, Dutta & Smita (2020) qualitative research also identified issues concerning online studies which include limited access to the internet, high cost of internet, unavailability of electronic devices, and students facing difficulties in using online platforms. Alvarez (2020) phenomenological research and Alipio (2020) descriptive study also supports the argument on how poor internet access, financial constraints, and lack of technological devices have been the demanding challenges among learners when exposed to emergency remote learning.…”
Section: Challenges Of Online Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In university level, the challenge of using online platforms has been valuable insights into the existing online tertiary scenario have also been provided Education continues in the form of COVID-19. [4] As the pandemic interfered with their academic functioning, students endured major education disturbances [5]. Face-to-face teaching/learning has been suspended since the closing of tertiary-level educational institutions.…”
Section: Introductionmentioning
confidence: 99%